Virmentalness: Prototype of Therapy for Dysthymia Patients Using Virtual Reality - Lovely Sepang; Jeine lambani; Rischa Tandiseru; I Gede Purnawinadi; Andria Wahyudi (CogITo Smart Journal, 2021)
AbstractDepressive disorders can happen to anyone and will affect the pattern of life. However, there are still people who underestimate depression itself. Generally, depression problems or mental disorders are carried out with psychotherapy, a method for treating problems to find out the experienced problem and using anti-depressants. This study aims to produce a therapeutic aid for depression sufferers in this dysthymia by using Virtual Reality technology, which can be used by patients and medical experts, namely psychologists and psychotherapists, to use Virtual Reality-based therapy methods. The research method used is the prototyping method. The way to collect data is by interview and scientific literature. Researchers used Unity3D Software to create Virtual Reality applications. Virmentalness application is expected to help people with dysthymia symptoms in doing therapy to reduce symptoms. The application displays a 3D viewing environment of a room, a 360-degree atmosphere, and content video and audio for therapy methods. Keywords— Depressive disorders, Dysthymia, Virtual Reality, Therapy, Android